A Frontier Enclave between the Hispanic Provinces: The Elusive Definition of Bastetania and the Bastetani Ethnic Identity in the Second Century BC - García Cardiel, Jorge (Gerión. Revista de Historia Antigua, 2021)
The present study deals with the political, social, economic and cultural dimensions of the local communities of Iberian Bastetania in the immediate aftermath of the Roman conquest. Bastetanian valleys and basins were a rearguard zone during the Second Punic War, and since then they were a peripheral region, halfway between the two Hispanic provinces. That, combined with the difficulties in communications and the complex orography, made this zone a frontier enclave with strong personality. Hence the substantial differences between Bastetanian structures and the (even more) hybrid structures that had begun to emerge in the surrounding regions a lot earlier.